2022
DOI: 10.2967/jnumed.122.263861
|View full text |Cite
|
Sign up to set email alerts
|

Antibody Engineering for Nuclear Imaging and Radioimmunotherapy

Abstract: Radiolabeled antibodies have become indispensable tools in nuclear medicine. However, the natural roles of antibodies within the immune system mean that they have several intrinsic limitations as a platform for radiopharmaceuticals. In recent years, the field has increasingly turned to antibody engineering to circumvent these issues while retaining the manifold benefits of the immunoglobulin framework. In this "Focus on Molecular Imaging" review, we cover recent advances in the application of antibody engineer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 39 publications
0
11
0
Order By: Relevance
“…Because NSG mice were used instead of nude mice for two of the murine models used in the PET imaging studies, the metastatic and PDXs, one additional structural modification was needed for the immunoconjugate. We have previously reported that NSG mice (which lack endogenous mIgG) exhibit very high uptake of radioimmunoconjugates in the liver and spleen, presumably because circulating and tissue-resident macrophages with unoccupied mFcγRI receptors bind the radiolabeled antibodies and sequester them in these organs. , We have found that this phenomenon can be avoided via the deglycosylation of immunoconjugates as the removal of the heavy chain glycans abrogates FcγRI binding, thereby helping radioimmunoconjugates avoid capture by mFcγRI-bearing myeloid cells and reducing their consequent accretion in the spleen and liver. , While we do not yet know if this phenomenon extends to human patients, reducing the uptake of the radioimmunoconjugate in the spleen and liver in this way could significantly reduce radiation dose rates to these tissues, thereby preventing side effects such as radiation-induced liver disease . For this study, DFO-αCD133 was deglycosylated with PNGase F to create degly DFO-αCD133, and the deglycosylation was confirmed via SDS-PAGE (Figure S1).…”
Section: Resultsmentioning
confidence: 99%
“…Because NSG mice were used instead of nude mice for two of the murine models used in the PET imaging studies, the metastatic and PDXs, one additional structural modification was needed for the immunoconjugate. We have previously reported that NSG mice (which lack endogenous mIgG) exhibit very high uptake of radioimmunoconjugates in the liver and spleen, presumably because circulating and tissue-resident macrophages with unoccupied mFcγRI receptors bind the radiolabeled antibodies and sequester them in these organs. , We have found that this phenomenon can be avoided via the deglycosylation of immunoconjugates as the removal of the heavy chain glycans abrogates FcγRI binding, thereby helping radioimmunoconjugates avoid capture by mFcγRI-bearing myeloid cells and reducing their consequent accretion in the spleen and liver. , While we do not yet know if this phenomenon extends to human patients, reducing the uptake of the radioimmunoconjugate in the spleen and liver in this way could significantly reduce radiation dose rates to these tissues, thereby preventing side effects such as radiation-induced liver disease . For this study, DFO-αCD133 was deglycosylated with PNGase F to create degly DFO-αCD133, and the deglycosylation was confirmed via SDS-PAGE (Figure S1).…”
Section: Resultsmentioning
confidence: 99%
“…One significant benefit of using radiolabeled antibodies is their ability to selectively target cancer cells that express certain antigens inside the tumor mass. 13 This approach allows the feasibility of destruction of a larger number of cells via the crossfire effect of radiation, even those that do not display the targeted antigen. The use of monoclonal antibodies that are tagged with β-emitting radionuclides has shown a synergistic effect, combining radiation-induced cytotoxicity to efficiently kill tumor cells.…”
Section: Discussionmentioning
confidence: 99%
“…One significant benefit of using radiolabeled antibodies is their ability to selectively target cancer cells that express certain antigens inside the tumor mass 13 . This approach allows the feasibility of destruction of a larger number of cells via the crossfire effect of radiation, even those that do not display the targeted antigen.…”
Section: Discussionmentioning
confidence: 99%
“…They are a key receptor in the immune system (Nicholson 2016) and genetic variation drives the humoral adaptive immune response in vaccination, infection, and autoimmunity (Mikocziova et al 2021). Due to this importance, antibodies are actively being researched to understand their correlates of protection for various diseases (Huang et al 2020) (Plotkin 2023) and ability to neutralize pathogens (Gumah Ali et al 2020), to utilize antibody indexes to diagnose viral infections (Shamier et al 2021), to apply them to various types of imaging (Rodriguez et al 2022) (Im et al 2019), and to engineer immunotherapeutics for a wide variety of pathologies, such as cancers (Scott et al 2012) (Zinn et al 2023; Lucas et al 2021) and autoimmune diseases (Carter and Rajpal 2022). Research into understanding and engineering antibody binding is largely focused on their Complementary Determining Regions (CDRs), hypervariable regions that predominantly determine their binding repertoires (Peng et al 2022) (Chiu et al 2019).…”
Section: Introductionmentioning
confidence: 99%